Adult Gannet migrations frequently loop clockwise around Britain and Ireland. Issue 1 (2nd January 2018) - Furness, Robert W.; Hallgrimsson, Gunnar T.; Montevecchi, William A.; Fifield, David; Kubetzki, Ulrike; Mendel, Bettina; Garthe, Stefan
ABSTRACT: The Gannet Morus bassanus is one of the seabirds considered most at risk from collision mortality at offshore wind farms in UK waters, so a better understanding of migration routes informs assessments of risk for different populations. Deployment of geolocators on breeding adults at the Bass Rock, Scotland, and Skrúður, Iceland, showed that the timing of migrations differed between populations, birds from Bass Rock passing south through UK waters mostly in October and back in February while birds from Skrúður passed south through UK waters mostly later, in November, but returned north earlier, in January. Many birds from both colonies made a clockwise loop migration around Britain and Ireland. Only a minority of birds from the Bass Rock returned northwards to the colony through the southern North Sea. A counter-intuitive consequence is that many Gannets moving northwards through waters to the west of Britain and Ireland in spring may be birds from North Sea colonies. Although Gannets normally remain over the sea, one tracked bird appears to have made a short overland passage in spring from the west of Scotland through central Scotland to the Bass Rock, whereas most returned around the north of Scotland.